Manual on wooden packaging : special programme for export packaging - Harvey, John D. (ITC. UNCTAD/GATT GenevaCH, 1986)
Textbook on design and manufacture of wooden packaging. Discusses world timber resources and production, species suitable for packaging use, use criteria, wood faults, wood products for packaging use; assembly and fastening methods; boxes, cases, crates, trays and boxes for fresh fruit and vegetables; pallets; international markings; testing and research.